(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Interstitial lung diseases (ILDs) encompass a diverse group of disorders that affect the lung parenchyma or interstitium, leading to inflammation and progressive scarring of lung tissue. This process results in thickening and stiffening of the lung tissue, impairing the lungs’ ability to expand and fill with air. As occupational disorders rise in society, particularly conditions like ILD, there is an increasing need for preventive healthcare approaches. While current invasive diagnostic methods and therapeutic interventions offer certain benefits, they often come with drawbacks such as side effects and high costs. Ayurvedic medicine, with its holistic focus on prevention and individualized treatment, offers a promising alternative. By addressing underlying imbalances and promoting overall wellness, Ayurvedic remedies could provide a feasible and effective solution for managing symptoms of ILD and preventing its progression, aligning with modern healthcare’s push towards more natural and sustainable care practices.